Targeted Genome Mining Reveals the Psychrophilic Clostridium estertheticum Complex as a Potential Source for Novel Bacteriocins, Including Cesin A and Estercticin A - Wambui, Joseph; Stevens, Marc J. A.; Sieber, Simon; Cernela, Nicole; Perreten, Vincent; Stephan, Roger (Frontiers in Microbiology, 2022)
Antimicrobial resistance in pathogenic bacteria is considered a major public health issue necessitating the discovery of alternative antimicrobial compounds. In this regard, targeted genome mining in bacteria occupying under explored ecological niches has the potential to reveal such compounds, including bacteriocins. In this study we determined the bacteriocin biosynthetic potential of bacteria from the psychrophilic Clostridium estertheticum complex (CEC) through a combination of genome mining and phenotypic screening assays. The genome mining was perfomed in 40 CEC genomes using antiSMASH. The production of bacteriocin-like compounds was phenotypically validated through agar well (primary screening) and disk diffusion (secondary screening) assays using cell free supernatants (CFS) and partially purified extracts, respectively. Stability of four selected CFS against proteolytic enzymes, temperature and pH was determined while two CFS were analyzed by HRMS and MS/MS to identify potential bacteriocins. Twenty novel bacteriocin biosynthetic gene clusters (BBGC), which were classified into eight (six lantibiotics and two sactipeptides) distinct groups, were discovered in 18 genomes belonging to C. estertheticum (n=12), C. tagluense (n=3) and Genomospecies2 (n=3). Primary screening linked six BBGC with narrow antimicrobial activity against closely related clostridia species. All four preselected CFS retained activity after exposure to different proteolytic, temperature and pH conditions. Secondary screening linked BBGC1 and BBGC7 encoding a lantibiotic and sactipeptide, respectively, with activity against Bacillus cereus while lantibiotic-encoding BBGC2 and BBGC3 were linked with activity against B. cereus, Staphylococcus aureus (methicillin resistant), Escherichia coli and Pseudomonas aeruginosa. MS/MS analysis revealed that C. estertheticum CF004 produces cesin A, a short natural variant of nisin, and HRMS indicated the production of a novel sactipeptide named estercticin A. Therefore, we have shown the Clostridium estertheticum complex, in particular C. estertheticum, as a source of novel and stable bacteriocins that have activities against clinically relevant pathogens.